Penerapan Data Mining untuk Menentukan Ketersediaan Stok Barang Berdasarkan Permintaan Konsumen di PT Indonesia Thai Summit Plastech Menggunakan K-Means Clustering - Azis, Abd; Sutisna (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
Inventory is one of the important things for companies because most of the company's activities are embedded in inventory, with various kinds of problems that exist internally and externally, between employees and superiors and between the company and customers, one of which is inventory problems. So, by having a company's inventory that is stable and in line with customer needs, it will be able to prevent problems between the company and its customers and maintain the company's survival. From the results of research carried out in checking stock availability at PT Indonesia Thai Summit Plastech, basically it is still manual, there is no system that can provide and make things easier for the company or warehouse department. With the problems mentioned above, a system is needed that is able to make it easier and provide information to the company or warehouse quickly. The results of this research produce an output in the form of stock availability patterns, stock accuracy or inventory by applying data mining using the k means clustering method.